Micro‐electro‐mechanical systems capacitive ultrasonic transducer with a higher electromechanical coupling coefficient. (1st October 2015) - Miao, Jing; Shen, Wenjiang; He, Changde; Xue, Chenyang; Xiong, Jijun
Abstract : Since the proposing of capacitive micromachined ultrasonic transducer by Khuri Yakub group in 1994 that this kind of transducer occupying the advantages of wide bandwidth, impedance matching well with the propagation medium especially in fluid and air and high sensitivity, has shown a great potential for wide ranges of applications. This Letter reports kind of micro‐electro‐mechanical systems (MEMS) capacitive ultrasonic transducer with the novel cavities embedded in the device layer of silicon on insulator wafer bonded with a glass substrate. The optimum geometric dimensions are confirmed by both mechanical vibrating of the membrane and the electrical characteristics analysis. Finite‐element analysis is adopted to determine the operation mode. The safety and reliability of the proposed device is ensured by the obtained deflections and equivalent stress under operation/collapse voltage. The bottom electrodes of the proposed transducer are fabricated on the top surface of the glass substrate. The parallel parasitic capacitance is reduced, thus improving the electromechanical coupling coefficient. The test results show that the electromechanical coupling coefficient is 69.65%, which demonstrates that this proposed MEMS capacitive ultrasonic transducer structure can enhance the performance significantly.